Wired/Wireless Internet Communication 10th International Conference, WWIC 2012, Santorini, Greece, June 6-8, 2012. Proceedings - Koucheryavy, Yevgeni; Mamatas, Lefteris; Matta, Ibrahim; Tsaoussidis, Vassilis; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 10th International Conference on Wired / Wireless Internet Communications, WWIC, held in Santorini island, Greece during June 6-8, 2012. The 23 revised full papers and 6 short papers presented were carefully reviewed and selected from 50 submissions. The papers are organized in six thematically-distinct technical sessions, covering the following major topics: virtual networks and clouds, multimedia systems, wireless sensor networks and localization, delay-tolerant and opportunistic networks, handover techniques and channel access, and ad hoc networks
Keywords: Computer science; Computer Communication Networks; Software engineering; Data protection; Information systems; Computer Science; Computer Communication Networks; Information Systems Applications (incl. Internet).; Information Systems and Communication Service; Software Engineering; Systems and Data Security